Putting up a good fight: The Galí-Monacelli model versus "The six major puzzles in international macroeconomics" - Stefan Ried (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
In this paper, the following question is posed: Can the New Keynesian Open Economy Model by Galí and Monacelli 2005b) explain "Six Major Puzzles in International Macroeconomics", as documented in Obstfeld and Rogoff (2000b)? The model features a small open economy with complete markets, Calvo sticky prices and monopolistic competition. As extensions, I explore the effects of an estimated Taylor rule and additional trade costs. After translating the six puzzles into moment conditions for the model, I estimate the five most effective parameters using simulated method of moments (SMM) to fit the moment conditions implied by the data. Given the simplicity of the model, its fit is surprisingly good: among other things, the home bias puzzles can easily be replicated, the exchange rate volatility is formidably increased and the exchange rate correlation pattern is relatively close to realistic values. Trade costs are one important ingredient for this finding.
Keywords: F41; F42; E52; 330; International Macroeconomics; New Keynesian open economy model; trade costs; simulated method of moments (SMM); Neue Makroökonomik offener Volkswirtschaften; Ungleichgewichtstheorie; Simulation; Außenwirtschaftstheorie; Offene Volkswirtschaft; Kosten; Theorie